2014
DOI: 10.1111/ejn.12679
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down inputs from the olfactory cortex in the postprandial period promote elimination of granule cells in the olfactory bulb

Abstract: Elimination of granule cells (GCs) in the olfactory bulb (OB) is not a continual event but is promoted during a short time window in the postprandial period, typically with postprandial sleep. However, the neuronal mechanisms for the enhanced GC elimination during the postprandial period are not understood. Here, we addressed the question of whether top-down inputs of centrifugal axons from the olfactory cortex (OC) during the postprandial period are involved in the enhanced GC elimination in the OB. Electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Previous experiments have demonstrated that OC‐SPWs generated in the PC can be observed in other olfactory‐related brain areas, such as the olfactory tubercle (Narikiyo et al., ) and OB (Manabe et al., ). It has been reported that pharmacological and electrical manipulation of top‐down inputs from the PC to the OB during postprandial sleep affected plastic changes in intrabulbar circuits, by regulating the elimination of newly generated granule cells in the OB as a function of a prior waking experience (Komano‐Inoue et al., ; Yokoyama et al., ). As granule cells play an important role in odor discrimination by modulating secondary olfactory neurons (Shepherd, Chen, Willhite, Migliore, & Greer, ; Yokoi, Mori, & Nakanishi, ), re‐organization of granule cells through top‐down inputs from the PC during the postprandial sleep period may be important for olfactory information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have demonstrated that OC‐SPWs generated in the PC can be observed in other olfactory‐related brain areas, such as the olfactory tubercle (Narikiyo et al., ) and OB (Manabe et al., ). It has been reported that pharmacological and electrical manipulation of top‐down inputs from the PC to the OB during postprandial sleep affected plastic changes in intrabulbar circuits, by regulating the elimination of newly generated granule cells in the OB as a function of a prior waking experience (Komano‐Inoue et al., ; Yokoyama et al., ). As granule cells play an important role in odor discrimination by modulating secondary olfactory neurons (Shepherd, Chen, Willhite, Migliore, & Greer, ; Yokoi, Mori, & Nakanishi, ), re‐organization of granule cells through top‐down inputs from the PC during the postprandial sleep period may be important for olfactory information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, selection of new GCs occurs during specific behaviors, and is promoted by the centrifugal inputs from the OC during the behaviors (Figure 1). For example, elimination of new GCs is enhanced during the sleep period after eating, and is dependent on the centrifugal inputs from the OC during post-meal sleep (Yokoyama et al, 2011; Yamaguchi et al, 2013; Komano-Inoue et al, 2014). GC elimination is also enhanced by the delivery of an electrical foot shock, depending on the centrifugal inputs from the OC during startle and fearful responses (Komano-Inoue et al, 2015).…”
Section: Olfactory Bulb Integrates Peripheral Odor Inputs and Centralmentioning
confidence: 99%
“…reported that pharmacological and electrical manipulation of top-down inputs from the PC to the OB during postprandial sleep affected plastic changes in intrabulbar circuits, by regulating the elimination of newly generated granule cells in the OB as a function of a prior waking experience(Yokoyama et al, 2011;Komano-Inoue et al, 2014). As granule cells play an important role in odor discrimination by modulating secondary olfactory neurons(Yokoi et al, 1995;Shepherd et al, 2007) , re-organization of granule cells through top-down inputs from the PC during the postprandial sleep period may be important for olfactory information processing.…”
mentioning
confidence: 99%